The eﬀect of nickel phytotoxicity on photosystem II activity and antioxidant enzymes in barley - Doğru, Ali; Altundağ, Hüseyin; Dündar, Mustafa Şahin (Acta Biologica Szegediensis, 2021)
In this study, the eﬀect of mild (100 µM), moderate (300 µM) and severe (500 µM) nickel (NiSO4.7H2O) toxicity on the photosynthetic activity, photosynthetic pigment content and some antioxidant enzymes in the leaves of a barley cultivars (Hordeum vulgare L. cv. Tarm-92) was investigated. Moderate and severe nickel toxicity decreased root length while shoot length was not aﬀected by nickel stress, probably due to over accumulation of nickel in roots. Similarly, biomass accumulation was declined by moderate and severe nickel toxicity as reﬂected by the lowered fresh and dry weight. Chlorophyll a, chlorophyll b and consequently total chlorophyll content decreased by all nickel applications, presumably because the reduced level of carotenoids. Chlorophyll a ﬂuorescence measurements showed that nickel toxicity blocked electron movement in some speciﬁc points of the photosynthetic electron transport system. The constant Fo value indicated that PSII reaction centers was not damaged in the leaves of barley under nickel toxicity while the reduced Fm value showed that acceptor side of PSII was more sensitive to nickel toxicity as compared to donor side. Changes in JIP test parameters in the leaves of barley showed that primary photochemical reactions are reduced, and thermal dissipation of excess energy is increased. SOD and CAT activity is elevated in the leaves of barley under moderate and severe nickel toxicity which demonstrate an eﬃcient superoxide dismutation. Severe nickel toxicity, however, did not aﬀect SOD and CAT activity. The ascorbate-glutathione cycle was activated in the leaves of barley plants under nickel toxicity, probably indicating an eﬃcient H2O2 detoxiﬁcation. However, considerable H2O2 and MDA accumulation was observed in the leaves of barley under nickel stress. As a result, it may be concluded that the barley genotype Tarm-92 is moderately tolerant to nickel toxicity.